Theorizing Land Ownership in Land Titling - Cuevas Jadina, Maribeth; Flor, Benjamina Paula G.; Quirejero, Nelson Jose Vincent; Jamias, Serlie B. (Silliman Journal, 2022)
The Philippine contemporary land ownership and titling system underwent severe reforms through several decades. In 1988, the Comprehensive and Agrarian Reform Law (CARL) was crafted aimed to distribute the country’s land base. After two decades, the government launched the land administration and management project (LAMP) to secure land tenure as well as reduce the country’s poverty rate. From 1988 to the current date, land reform programs created and disseminated a vast amount of knowledge from implementers that trickles down to the community. This paper aimed to identify and discuss the concept of land and land ownership through land titling and to determine its connotations after three decades of agrarian reform. Data was gathered through indepth interviews and was analyzed using the Atlas.ti. The results were interpreted within the context of constructivism. Three major paradigms emerged in the process. Land ownership through titling is viewed as security, pride, and propaganda.